Inclusive Sporting Events in Schools for Youth With Disabilities in Quebec: Social, Educational, and Experiential Roles of These Activities According to the Interviewed Practitioners. (3rd September 2015) - Roult, Romain; Brunet, Isabelle; Belley-Ranger, Émilie; Carbonneau, Hélène; Fortier, Julie
Participating in physical activities and sports entails positive impacts for youth with disabilities regarding their physical and social well-being. In Quebec, however, opportunities to practice inclusive sports adapted to their needs are scarce beyond the boundaries of the school environment. Through 33 semi-structured interviews conducted with practitioners involved in organizing such adapted sporting events, this study aims to better understand the needs and expectations linked to these events and, simultaneously, identify the social, experiential, and educational roles of these events on youth with disabilities. Results demonstrate substantial positive impacts on these young people (enjoyment, pride, self-esteem, etc.) and on their relatives. Results also highlight several barriers, notably, material and human, that can hinder their desire to go on with physical activities and sports in their school environment.